From business cards to business relationships : personal branding and profitable networking made easy, second edition - Graham, Allison Dawn, 1975- (John Wiley & Sons Canada, 2012)
Want to supercharge your life? Effective networking is the answer and this book will teach you how. Professionals of all stripes and ages are told to 'get out there' and network so they can build their careers, grow their businesses and elevate their influence in the community, but they are rarely taught the skills to do that. Most people are lost, intimidated by the idea of presenting their own personal brand, and frustrated when it comes to networking. Despite long hours at events and attempts to make the right connections, they aren't seeing their desired results.